Integrating ethnomathematics into challenge-based learning: A need assessment for enhancing students’ creative problem solving and scholarly zeal - Helma, Mustika; Ningsih, Sri Yunita (Journal of Didactic Mathematics, 2025)
This study aims to conduct a comprehensive needs assessment as the foundational phase in the development of an ethnomathematics-integrated Challenge-Based Learning (CBL) model, designed to enhance students' creative problem-solving (CPS) abilities and scholarly interest in mathematics. A qualitative descriptive approach was employed, with data collected through student questionnaires, teacher interviews, and documentary analysis of curricular materials. The findings reveal a significant gap between the current state of instruction and desired learning outcomes. Students exhibited critical deficits in CPS, particularly in connecting concepts to real-world contexts and devising alternative strategies, alongside a pronounced lack of intrinsic motivation (scholarly enthusiasm). Teachers identified the dominance of procedural, routine-based instruction as a primary cause, while simultaneously expressing a strong demand (84.6%) for innovative, contextual pedagogical models. The analysis underscores the potent, yet underutilized, potential of local cultural elements (ethnomathematics) to serve as authentic contexts for meaningful challenges. The study conclusively establishes that the integration of ethnomathematics within a CBL framework is a theoretically sound and empirically warranted strategy to address the identified gaps. This integration is projected to foster a more engaging, relevant, and effective mathematics learning environment that cultivates essential 21st-century competencies.